Transformation or Truce? Tracing the Decline of “reconciliation” and its consequences for Northern Ireland since 1998 - Morrow, Duncan (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2023)
Reconciliation and consociation were at the core of the Belfast/Good Friday Agreement (BGFA) in 1998. Analysis of the politics of the last 25 years in Northern Ireland (NI), however, reveals that many presumed aspects of reconciliation – integrated education, desegregated living, the disbandment of armed groups, cultural rapprochement, linguistic and cultural diversity, safe and secure shared public space, an approach to the past which puts the suffering of victims at its core – remain unaddressed or are deeply disputed. The article explores how consociational government in Northern Ireland has gradually decayed under pressure from this weakness. Since 2016, reconciliation has been a secondorder consideration for the shaping partnership between the United Kingdom (U.K.) and Ireland which made the Agreement possible, leaving the Agreement at risk from the repeated exercise of the veto and dependent on the absence of any alternative, rather than proactive commitment.
Keywords: konsociacija; Severna Irska; Sporazum iz Belfasta; sprava; Velikonočni sporazum; vključevanje spolov; vzpostavljanje miru